"Forging accounting principles" in France, Germany, Japan, and China: A comparative review. (November 2018) - Camfferman, Kees; Detzen, Dominic
This article surveys the English-language literature on the history of financial reporting regulation in four non-English-speaking countries: France, Germany, Japan, and China. The choice of these countries was based on the availability of a sizable accounting history literature in the area surveyed. We first offer a summary of regulatory events in the four countries and suggest that the literature provides ample evidence of the countries' intricate histories of financial reporting regulation. In addition, we point to important research gaps, where we believe that the literature has significant underexploited potential, in particular by moving beyond high-level overviews of changing regulatory mechanisms to in-depth studies of regulatory change that are embedded in the local legal, political, and societal contexts. Hence, plenty of opportunities exist for further research into these countries' regulatory histories, either in terms of single-country studies or as comparative histories.